Civara: The Politics of Dhammayuttika Nikaya Buddhism Robe Usage in Thailand - Pabhakaro, PhramahaPunsombat; Ariyametee, PhrabaidhikaChaatchawan; Peuchthonglanglang, Prateep (Interdisciplinary Academic and Research Journal, 2022)
The robe is derived from the word requiem robe. In the early age of the Lord Buddha, he only allowed his disciples to use the word requiem robe. it was later obtained from the villagers, but the robe pattern and robes remained unknown. On one occasion, the Buddha was walking through the Thaksina Khiri countryside when he came across a Bihar. As a result, Phra Anon was assigned to sew a robe in the Khanna style until it became an art form of clothing for Buddhist monks particularly those of the Theravada in Thailand. Vajirayan Bhikkhu (King Rama IV during his matriculation) founded the Dhammayuttika Nikaya in 1936, and he instituted customs and practices that differed from the original sect, such as the color of robes, patterns and methods of robe-covering, and so on. The Raman robe is worn by the Dhammayut sects as a symbol of pragmatism and political acceptance. Furthermore, the 2014 announcement regarding the use of robe colors requiring Phra Dhammayut sects throughout the diocese to wear royal-colored robes created a ripple effect and brought a concrete approach to the area of power.